2005
DOI: 10.1369/jhc.4b6510.2005
|View full text |Cite
|
Sign up to set email alerts
|

QF-PCR Examination of Parental and Meiotic Origin of Trisomy 21 in Central and Eastern Europe

Abstract: Study of parental/meiotic origin of free trisomy 21 in nuclear families from Russia (70 cases), Ukraine (32 cases), and 22 from Germany revealed maternal nondisjunction in 77.3% (Germany), 93.8% (Ukraine), and 91.4% (Russia), paternal origin in 13.6%, 6.2%, and 8.6%, respectively. Maternal meiosis I errors were found in 84.4% (Ukraine), 77.1% (Russia), paternal origin in 3.1% (Ukraine), 2.9% (Russia). Maternal meiosis II errors occurred in 9.4% and 14.3% and paternal in 3.1% and 5.7% in Ukraine and Russia, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Our findings confirm the model for DS origin found in other populations (Antonarakis, 1991;Gó mez et al, 2000;Petersen and Mikkelsen, 2000;Machatkova et al, 2005;Freeman et al, 2007;Ramírez et al, 2007;Ghosh et al, 2010). The obtained frequencies of maternal MIderived (86%) and MII-derived (14%) trisomy 21 were different from the study reported by Freeman et al (2007), but similar to the studies on Mediterranean and Eastern Europe populations (Gó mez et al, 2000;Machatkova et al, 2005). The discrepancy was probably due to both the small sample size and maternal age distribution covered by the study.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings confirm the model for DS origin found in other populations (Antonarakis, 1991;Gó mez et al, 2000;Petersen and Mikkelsen, 2000;Machatkova et al, 2005;Freeman et al, 2007;Ramírez et al, 2007;Ghosh et al, 2010). The obtained frequencies of maternal MIderived (86%) and MII-derived (14%) trisomy 21 were different from the study reported by Freeman et al (2007), but similar to the studies on Mediterranean and Eastern Europe populations (Gó mez et al, 2000;Machatkova et al, 2005). The discrepancy was probably due to both the small sample size and maternal age distribution covered by the study.…”
Section: Discussionsupporting
confidence: 91%
“…The post zygotic mitotic error was estimated about 2%. Very concordant results were also reported for Ukraine and Russian cohorts (Machatkova et al 2005), and Spanish cohort (Gomez et al 2000). Little difference among these datasets that does exist is probably due to sampling variation.…”
Section: Introductionsupporting
confidence: 76%
“…We were curious whether this epidemiological pattern of DS birth in Indian cohort is similar to that of other ethnically different populations reported earlier. We compared our Indian dataset with those of US (Allen et al, 2009), Spanish (Go´mez et al, 2000), Ukraine and Russian cohorts (Machatkova et al, 2005), using Fisher's exact test. We did not obtain any significant difference in any pair-wise test for maternal :paternal ratio.…”
Section: Discussionmentioning
confidence: 99%